Disrupting an imposed racial identity or performing the model minority? The pursuit of postsecondary education by young African immigrant men in Southern Ontario, Canada. Issue 5 (2nd September 2020) - Wilson-Forsberg, Stacey; Masakure, Oliver; Shizha, Edward; Lafrenière, Ginette; Mfoafo-M'Carthy, Magnus
ABSTRACT: This article examines how young African immigrant men in Southern Ontario cope with the dominant racial identity at school in an effort to improve their academic performance and access postsecondary education (PSE). Critical race theory in education is employed to explain how the young men distance themselves from stereotypes about Black masculinity by regulating their own behaviour and differentiating themselves from their Caribbean immigrant peers. Sixty-seven young men who had immigrated to Southern Ontario from several African countries over the last 10 years were interviewed individually and in focus groups for the study. The findings suggest that the research participants adopted a model minority status within an educational system that clearly embodies racist and systemically oppressive frameworks.